Cross-cultural Dialogues in Modernization Theory: The Impact of Western Philosophies upon Modern Confucianism in East Asia - S. Rošker, Jana (Two Homelands, 2013)
As a major source of social values, Modern Confucian theory has assumed great significance amidst the proliferation of instrumental rationalities in contemporary China. This neo-conservative current is distinguished by a multifaceted attempt to revitalize traditional thought by means of new influences borrowed or derived from Western systems. It is defined by a search for a synthesis between “Western” and traditional Chinese thought, aiming to elaborate a new system of ideas and values suitable for the modern, globalized society.